Comparison of Kidney Paired Donation Transplantations with Living Related Donor Kidney Transplantation: Implications for National Kidney Paired Donation Program. (May 2013) - Kute, Vivek B.; Gumber, Manoj R.; Vanikar, Aruna V.; Shah, Pankaj R.; Patel, Himanshu V.; Engineer, Divyesh P.; Modi, Pranjal R.; Rizvi, Jamal S.; Shah, Veena R.; Trivedi, Hargovind L.
<x xml:space="preserve">Abstract</x> Background: Kidney Paired Donation (KPD) is a rapidly growing modality for facilitating living related donor kidney transplantation (LRDKTx) for patients who are incompatible with their healthy, willing, and living donors. Data scarcity on the outcome of KPD versus LRDKTx prompted us to review our experience. Materials and methods: This was a single-center study of 224 patients on regular follow-up, who underwent LRDRTx from January 2010 to June 2012 at our institute. The aim of this study was to compare short-term graft survival, patient survival and rejection rates of KPD (group 1, n = 34) with those of LRDKTx (group 2, n = 190). All the recipients received triple immunosuppression and thymoglobulin induction in KPD group. Kaplan–Meier curves were used for survival analysis. In group 1, mean recipient age was 35.5 ± 13.2 years, 29 were men and mean donor age was 44.4 ± 8.17 years, 10 were men. In group 2, mean recipient age was 29.1 ± 10 years, 155 were men and mean donor age was 47.5 ± 9.69 years, 74 were men. Mean human leukocyte antigen (HLA) matching in group 1 and 2 was 1 versus 3.2 (p < 0.05). Results: One- and two-year patient survival showed no significant difference between the two groups (97.1%, 97.1% vs. 96.2%, 94.8%, respectively, p = 0.81). Death-censored graft survival also showed no significant difference between the two groups (97.1%, 97.1%, vs. 97.6%, 97.6%, p = 0.73). Acute rejection incidence was also similar (8.7% vs. 9.9%, p > 0.62). Conclusions: Our study showed similar graft survival, patient survival and rejection rates of KPD versus LRDKTx over 2 years post-transplantation, encouraging the use of this approach for national KPD program.